1992
DOI: 10.1017/s0952523800006465
|View full text |Cite
|
Sign up to set email alerts
|

Foveal dark adaptation, photopigment regeneration, and aging

Abstract: Foveal dark adaptation in 58 subjects and photopigment regeneration in 60 subjects from 10-78 years of age exhibit parallel slowing of recovery rate with increasing age, with significant correlation of the two functions among individuals. The data are suggestive of an initial slight decline in rate before age 50, followed by a greater decline occurring at different ages in different individuals. Longitudinal data for one subject from age 40-65 show an increase in pigment regeneration time constant consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
27
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 50 publications
8
27
0
Order By: Relevance
“…In agreement with our findings, Coile & Baker [4] also demonstrated a greater variability in the rate of adaptation of older participants compared to younger ones. The increased variability could suggest that those apparently normal individuals with prolonged time constants may be at risk of developing ARM.…”
Section: Figures 2 and 3 About Heresupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with our findings, Coile & Baker [4] also demonstrated a greater variability in the rate of adaptation of older participants compared to younger ones. The increased variability could suggest that those apparently normal individuals with prolonged time constants may be at risk of developing ARM.…”
Section: Figures 2 and 3 About Heresupporting
confidence: 93%
“…The effect of age on recovery time constant in this study produced an increase of 27 seconds per decade (0.45 minutes / decade) which was comparable to the findings of Coile & Baker [4] who showed an increase of 0.21 minutes per decade. Although the relationship between age and time constants in this study can be fitted using a single linear function, it is possible that a steeper rate of change above 55 years may be present as suggested by Newsome et al [14].…”
Section: Figures 2 and 3 About Heresupporting
confidence: 90%
See 2 more Smart Citations
“…Previous studies have reported age-related decreases in photopigment OD based on reflection densitometry (Kilbride et al, 1986;Keunen et al, 1987;Coile & Baker, 1992) and color matching (Eisner et al, 1987;Elsner et al, 1988;Swanson & Fish, 1996). Because these aging studies have been conducted with trichromats, the photopigment OD of M-and L-cones may have been confounded.…”
Section: Introductionmentioning
confidence: 99%